2022
DOI: 10.2514/1.j061661
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Over-Tip-Rotor Liners for the Suppression of Fan Noise

Abstract: Fan noise is one of the dominant sources of aircraft engine noise, both at approach and at take-off. Improved attenuation of fan noise with acoustic liners and the reduction of fan noise at source remain key technology challenges for civil aviation in the foreseeable future. Over-Tip-Rotor (OTR) acoustic treatments have been investigated experimentally during the last decade and significant fan noise reductions have been measured, most recently using a single rotor and multiple lined circumferential grooves. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It was found that the source modification effects for the values of impedance investigated were most dominant for e/λ < 0.5, where e is the distance from the source to the liner wall and λ is the acoustic wavelength. This model was improved in (Palleja-Cabre et al, 2022a) to include the modelling of an inlet termination and distributed rotating sources and compared with the experimental results of Bozak and Dougherty (Bozak and Dougherty, 2018). More recently, this problem was also studied analytically by Sun et al (Sun et al, 2022) by using a coupled singularity method.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the source modification effects for the values of impedance investigated were most dominant for e/λ < 0.5, where e is the distance from the source to the liner wall and λ is the acoustic wavelength. This model was improved in (Palleja-Cabre et al, 2022a) to include the modelling of an inlet termination and distributed rotating sources and compared with the experimental results of Bozak and Dougherty (Bozak and Dougherty, 2018). More recently, this problem was also studied analytically by Sun et al (Sun et al, 2022) by using a coupled singularity method.…”
Section: Introductionmentioning
confidence: 99%